Charitable giving among females and males: An empirical test of the competitive altruism hypothesis - Robert Böhm; Tobias Regner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
We conduct a real-effort task experiment where subjects' performance translates into a donation to a charity. In a within-subjects design we vary the visibility of the donation (no/private/public feedback). Confirming previous studies, we find that subjects' performance increases, that is, they donate more to charity, when their relative performance is made public. In line with the competitive altruism hypothesis, a biology-based explanation for status-seeking behavior, especially male subjects increase performance in the public setting.
Keywords: C91; D03; J16; 330; social preferences; other-regarding behavior; charitable giving; social-image concerns; competitive altruism; experiments; social status; Spende; Altruismus; Sozialer Status; Geschlecht; Test